LOWCOST VHF AIRBAND TRANSCEIVER KOMUNIKASI ATC DAN PENERBANG UNTUK BANDARA KECIL - Nyaris Pambudiyatno; Totok Warsito; Bambang Bagus Harianto (Jurnal Penelitian)
In this study a prototype will be made for VHF airband, the design used uses GNURadio installed on the Windows operating system as digital signal processing, and the digital data that comes out will be converted into analog using Software Defined Radio (SDR). The modulation used is Amplitude Modulation (AM) on the Audio Source transmitter system with a sample rate of 48kHz, using Multiply Const 1.2 and Signal Source 500mV on the signal receiver, the average modulation percent value is 0.8